The role of determining the economic quantity of the demand in reducing the total costs of inventory A case study in the Institute of Technical Management / Baghdad - حسين احمد ابراهيم (Journal of Economics and Administrative Sciences, 2019)
ABSTRACT The research aims to identify the role of scientific planning of inventory by determining the quantity of economic demand and the number of times of purchase and associated annual total costs to achieve a sufficient and appropriate level of inventory . The research was based on the case study methodology. Materials of increasing demand in the Institute of Technical Management and knowledge of the degree of conformity of the procurement plan with the standard indicators adopted in a scientific method ,its include economic order quantity and number of purchasing times . one of The main results of the research was the existence of a large difference between the quantity of the economic purchase of each of the items of the materials in search and the actual quantity purchased by the organization during the year